Clinical rationale of diagnostic approaches in the dental examination of dogs - U. І. Voloboieva; D. D. Bilyi (Theoretical and Applied Veterinary Medicine)
Currently, more than 70% of dogs examined in veterinary medicine hospitals have dental diseases, in 30% of cases their course is assessed as severe. The significant spread of dental pathology is due, first of all, to the imperfection of diagnostic approaches, which reduces the possibility of their detection in the early stages. The manuscript presents the clinical information value study results of various diagnostic methods of oral cavity diseases in dogs: dental trauma, plaque/tartar, dental caries, malocclusion, missing teeth, tooth dislocation, periodontal disease, the jaw bones osteomyelitis. It has been established that the simultaneous course of several diseases, which can develop independently of each other or be related: primary/secondary disease, complicates their diagnosis. Etiological factors must be taken into the account to carry out the differential diagnosis in each individual case. A significant variety of the causes of dental diseases associated with congenital or acquired factors makes it advisable to carry out a full range of diagnostic measures: analysis of anamnestic data – clinical examinations – radiography, probing. An integrated approach to the oral cavity diagnostics allows to identify concomitant diseases and complications of the underlying pathological process at early stages, and to increase the treatment effectiveness accordingly. For differential diagnosis of diseases that have a high risk of inflammation transition to nearby anatomical structures/tissues and active participation of pathogenic microflora in the pathogenesis, it is advisable to assess regional lymph nodes. Thus, the results obtained justify the need for dental examination under sedation and/or anaesthesia; combined use of clinical research methods and diagnostic equipment for visual study; consideration of the possibility of the pathological process spreading to adjacent tissues with the development of a disease that complicates the course of the underlying disease. The prospect of further research is the substantiation and clinical application of 3D tomography in veterinary dentistry.